Ekranisasi dalam Novel Ibu, Doa Yang Hilang Karya Bagas Dwi Bawono ke Film Just Mom yang Disutradarai oleh Jeihan Angga dan Implikasi terhadap Pembelajaran Sastra di SMK Negeri 3 Palangka Raya - Rina Mustika Dwi Listiani; Alifiah Nurachmana; Linggua Sanjaya Usop; Yuliati Eka Asi; Stefani Ratu Lestariningtyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The aim of this research is to describe: (1) the ecranization of the plot in the novel Ibu, Doa Yang Lost by Bagas Dwi Bawono to the film Just Mom directed by Jeihan Angga, (2) the ecranization of the characters in the novel Ibu, Doa Yang Lost by Bagas Dwi Bawono to the film Just Mom directed by Jeihan Angga, (3) the adaptation of the setting in the novel Ibu, Doa Yang Lost by Bagas Dwi Bawono to the film Just Mom directed by Jeihan Angga, (4) the implications of research results for literature learning at SMK Negeri 3 Palangka Raya. The approach used in this research is a qualitative descriptive method which describes using words, phrases, sentences and paragraphs regarding plot exranization, character exranization, setting setting and the implications of research results for literature learning at SMK Negeri 3 Palangka Raya with an independent learning curriculum. using teaching modules set in class. The results of the research regarding the ecranization process that occurred from the novel Ibu, Doa Yang Lost by Bagas Dwi Bawono to the film Just Mom, directed by Jeihan Angga, are as follows. 1) Excreation of the plot in the novel Ibu, Doa Yang Sembilan by Bagas Dwi Bawono into the film Just Mom directed by Jeihan Angga, there are 80 research data with 38 results of plot reduction, 39 results of plot additions, and 3 results of changes to various plots. 2) Excreation of the characters in the novel Ibu, Doa Yang Sembilan by Bagas Dwi Bawono into the film Just Mom directed by Jeihan Angga, there are 23 research data with 13 results of reducing characters, 7 results of adding characters, and 3 results of changing various characters. 3) Excreation of the setting in the novel Ibu, Doa Yang Sembilan by Bagas Dwi Bawono to the film Just Mom directed by Jeihan Angga, there are 20 research data with 13 reductions in the setting, 5 additions to the setting, and 2 changes to various settings. 4) This research can have implications for literature learning in SMK/MAK class Other Literature, namely Drama Texts.